Antiviral medicinal plants of India as a potential tool against COVID-19: A review with ethno scientific evidence - Mishra, D.; Kumar, A.; Tiwari, A.; Deepika; Chaturvedi, P. (Journal of Medicinal Herbs and Ethnomedicine, 2023)
Indian traditional medicinal systems are one of the oldest therapeutic systems in the world. Medicinal and aromatic plants play a dominant role in Indian traditional medicinal systems. Traditionally, many medicinal plants are used in India for their therapeutic relevance so much so that they have acquired a significant role in Indian religion as well. Many of these plants have proven antiviral effects. This review documents up-to-date information about many such medicinal herbs used in India which have got pharmacological significance in fighting viral infections. These plants surely have the potential to provide protection against Covid-19. The review presents a list of such plants along with their chemical ingredients and possible modes of action against the respective viral diseases. All information has been obtained by consulting the databases of Scopus, PubMed, Science Direct, Elsevier, Springer and relevant research papers and reports on COVID-19. The cited medicinal plants are used extensively in India as herbal remedies. The use of these plants is validated in light of research papers citing their ethnobotanical uses, important active principles and modes of action of the of medicinally important natural products. The plants listed have great potential to fight COVID-19 and other viral infections. Many of these are immunity boosters providing strength to the body to control the onset of diseases.